2013
DOI: 10.1590/s0104-530x2013000200013
|View full text |Cite
|
Sign up to set email alerts
|

Gestão de portfólio de projetos: contribuições e tendências da literatura

Abstract: A necessidade crescente de melhores resultados com recursos cada vez mais escassos requer que as empresas selecionem e invistam apenas nos projetos capazes de gerar vantagem competitiva. O fato de este processo de seleção envolver interesses e riscos, uma efetiva gestão de portfólio de projetos pode fornecer suporte de forma estruturada e organizada. Este trabalho tem como objetivo traçar um panorama da literatura acadêmica em gestão de portfólio de projetos, descrevendo tendências e os principais temas aborda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 82 publications
0
18
0
5
Order By: Relevance
“…In this sense, the implementation rate of the strategy tends to improve through project portfolio management (Buys and Stander, 2010), supporting companies to achieve better results, even with increasingly scarce resources. It is perceived that an effective project portfolio management can provide support in a structured and organized way in order to select only projects capable of generating competitive advantage, the organizations' desire to excel in the market (Carvalho et al, 2013).…”
Section: Implementing the Strategy Through Processes And Projectsmentioning
confidence: 99%
“…In this sense, the implementation rate of the strategy tends to improve through project portfolio management (Buys and Stander, 2010), supporting companies to achieve better results, even with increasingly scarce resources. It is perceived that an effective project portfolio management can provide support in a structured and organized way in order to select only projects capable of generating competitive advantage, the organizations' desire to excel in the market (Carvalho et al, 2013).…”
Section: Implementing the Strategy Through Processes And Projectsmentioning
confidence: 99%
“…By late 90's, with the rise in both the quantity and the complexity of the project scope, organizations started to be concerned about aligning projects to the organization's goals. That is when the importance assigned to the project portfolio management grew (Carvalho et al, 2013).…”
Section: Project Portfolio Managementmentioning
confidence: 99%
“…However, too many thoughts and projects that emerged in organizations outnumber the available financial resources. That requires a method to support the selection process, as it is the case of the multicriteria methods (Archer & Ghasemzadeh, 1999;Almeida & Duarte, 2011;Carvalho et al, 2013). This requirement is even more relevant to government entities which are accountable for managing public funds to provide society with significant results.…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review on the subject, Carvalho et al (2013) observed that the most cited methods and tools are financial, mathematical programming, and statistical models; and the criteria for the selection of projects that stand out most are now based on market potential, economic-financial analysis, and risk/ uncertainty analysis. Jugend et al (2014) propose a framework for project portfolio decision-making based on the systematic application of financial methods, checklists, scoring and prioritization models, diagrams and graphs, and market research.…”
Section: Environmental Sustainability and Project Portfolio Managementmentioning
confidence: 99%